Results of transanal endoscopic resections in rectal cancer - Nikitenko, R.; Vorotyntseva, K.; Degtiarenko, S.; Mishchenko, V.; Stepanovichus, E. (Journal of Education, Health and Sport, 2022)
Introduction. Rectal cancer is the most widespread form of cancer in different countries of the world, without regard to gender, and reaches 8–9% of the total number of all cancers. It is necessary to further improve and study modern methods of both surgical and combined integrated approach to the treatment of patients with rectal cancer. Lymphatic cancer spread is one of the most important causes of local recurrence of rectal cancer and an unfavorable prognostic. Aim of the study: to study and improve the results of treatment of patients with rectal cancer during transanal endoscopic microsurgery with staining “sentinel” lymph nodes. Materials and methods. In the period from 2009 to 2021, 92 patients with rectal cancer were operated on at the Odessa Regional Clinical Hospital using transanal endoscopic resections. All 92 patients were divided into 2 groups. In group I, 45 patients were diagnosed stage I rectal cancer (T1-2N0M0. In group II, 47 patients were diagnosed stage II rectal cancer (T3N0M0) before surgery. In group I, a standard TEM procedure was performed. In group II, taking into account the presence of stage II RC in patients, and the high possibility of recurrence and metastasis, after performing local excision of tumors using the TEM method, we improved this method. Results. The average time of the hospital stay was (3.4±1.7) days (from 2 to 6 days). The lower edge of the tumor was at the average height of (9.5±4.2) cm from the anal canal (from 5 to 18 cm), the average size of the tumor was from (2.8±1.7) cm (from 1.5 to 4 cm). The average follow-up period ranged from 12 to 60 months. Recurrence of rectal cancer was found in 6 (6.5%) patients, group I. Conclusions. One of the most important prognostic factors of the development of the RC local recurrence is the regional lymph nodes involvement. Identification and target study of the “sentinel” LN in patients with RC most likely make it possible to assess the stage of the disease and apply an adequate scheme of the complex treatment.